2014
DOI: 10.12944/crnfsj.2.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Anti-nutrients Contents of Edible Vegetables Under Varied Temperature and Heating Time

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…It is interesting to note that this sample fits into the above requirements of low oxalate and moderately high calcium contents food material. The value of oxalate obtained in this present study is lower than the lethal dose reported by Udosoro et al [34]. Tannin value of 0.49± 0.01 mg/g is lower than the amount reported for mango seed [25].…”
Section: Sugar Analysiscontrasting
confidence: 84%
See 1 more Smart Citation
“…It is interesting to note that this sample fits into the above requirements of low oxalate and moderately high calcium contents food material. The value of oxalate obtained in this present study is lower than the lethal dose reported by Udosoro et al [34]. Tannin value of 0.49± 0.01 mg/g is lower than the amount reported for mango seed [25].…”
Section: Sugar Analysiscontrasting
confidence: 84%
“…Tannins are capable of leaving available protein by antagonistic competition and can elicit protein deficiency syndrome commonly called kwashiorkor [35]. Boiling has been reported to be a very good means of reducing tannin contents of food materials [34]. The values obtained for flavonoids and total phenols were 7.89±0.10 mg/g and 6.25±0.01 mg/g respectively.…”
Section: Sugar Analysismentioning
confidence: 99%
“…Protease inhibitors are easily denatured by heat treatment due to their protein nature [113]. Research has shown that antinutrient levels are reduced with controlled heating at a temperature less than boiling for at least 15 minutes [114]. Autoclaving can also drastically decrease the content of tannins, phytic acid, hydrogen cyanide, trypsin inhibitors and oligosaccharides [6].…”
Section: Sprouting (Germination)mentioning
confidence: 99%
“…Protease inhibitors are proteinaceous in nature and they get readily denatured by heat treatment [50]. Various studies have shown that reduced antinutrient amounts can be obtained by heating under controlled conditions, that is, when the temperature is needed to be maintained lower than that of boiling point for about 15 min [51]. Boiling of Bambara groundnut seeds for about 1 h greatly decreased the amount of raffinose and also enhanced protein digestibility of seeds was obtained [52].…”
Section: Cookingmentioning
confidence: 99%